KOMBINASI MODEL QUANTUM DAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN MENULIS CERITA FANTASI DI SMP KELAS VII - Andi Sulfana Masri; Rahayu Pristiwati Pristiwati; Agus Nuryatin Nuryatin (STKIP Siliwangi, 2022)
This research is motivated by the low writing ability of students at various levels of education, especially at the junior high school level. This study aims to describe the stages of planning, implementing, and evaluating learning to write fantasy stories using a combination of Quantum (QL) and Problem Base Learning (PBL) models in Class VII SMP. The research method used is descriptive qualitative. Data collection techniques through observation, interviews, and test assessments. The application of a combination of QL and PBL models is considered effective in learning to write fiction if the student who scores 75 is 75%. The results of this study are: 1) at the planning stage, the preparation of the combination model of QL and PBL has been adapted to class conditions, teacher and student conditions; 2) at the implementation stage, teachers and students have carried out all the learning steps in accordance with the learning design; 3) at the evaluation stage, the average score of students who have passed the KKM (Teaching Completeness Criteria) is 75%, so it can be said that the combination of QL and PBL learning models is effectively used in learning to write fantasy stories.